The Ogoh-Ogoh Tradition in Maju Sejahtera Village, Karang Bintang Subdistrict, Tanah Bumbu Regency (1985–2024) - Ni Made Febrianti Eka Putri; Melisa Prawitasari; Dewicca Fatma Nadilla; Rochgiyanti Rochgiyanti (STKIP Taman Siswa Bima, 2025)
The ogoh-ogoh tradition, originally rooted in Balinese Hindu culture, has also developed in transmigration areas such as Dusun 2, Maju Sejahtera Village, Karang Bintang Subdistrict, Tanah Bumbu Regency. This study addresses two main questions: how the ogoh-ogoh tradition was introduced into a transmigrant community, and how local residents interpret its meaning. Positioned to fill a gap in existing research, this study explores how Balinese Hindu traditions adapt outside of Bali. Using historical methods, the research follows four stages: heuristics, source criticism, interpretation, and historiography. Data were collected through interviews with ten key informants and field documentation. Findings show that ogoh-ogoh has been practiced since 1985 and has evolved in form, meaning, and participation—especially among youth organized under STT Vasudhaiva Kutumbakam. The ogoh-ogoh is viewed not only as a symbolic figure to drive away negative forces before Nyepi, but also as a medium for cultural expression, social solidarity, and community identity among Hindus in migration settings. This study demonstrates that tradition can adapt to new environments without losing its core essence. The results of this study are important for strengthening Balinese cultural identity in transmigrant areas. Future research may further explore interreligious relations and the transformation of cultural values through digital and social media.